Studi Kebijakan Pemerintah Terkait Penanganan Inflasi Dan Tingkat Pengangguran - M. Momon Ompu Citoro; Septina Kusumaningtyas; Trison Andreas Manullang (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
One of the most difficult issues for a country to avoid is reducing the unemployment rate, and this problem is often referred to as a multidimensional issue. Unemployment serves as a starting point for other social problems, such as criminal activity and other economic issues. A low unemployment rate reflects an improving standard of living for the population. Therefore, government policies are needed not only from a micro perspective but also from a macro perspective, considering the dynamic inflation rate. This report is used to analyze the dynamic relationship between inflation and the unemployment rate in Indonesia during the period 2019 - 2023. This period has caused a rather complex economic disruption, so the inflation-unemployment relationship may differ from classical economic theory. This study also compares the effectiveness of the Phillips curve on government policy. The data used are secondary data from the Central Statistics Agency (BPS), including the inflation rate and the open unemployment rate. The method of analysis used is descriptive quantitative. The research results show that there is a negative relationship between inflation and the unemployment rate in Indonesia during the period 2019 - 2023. This means that when inflation increases, the unemployment rate decreases, and vice versa. However, based on current real conditions, they are now aligned. Government policies aimed at controlling inflation need to consider their impact on the unemployment rate.